Red Star - Red Army Chorus and Dance Ensemble - Fulford, Jonathan
This concert, given by the magnificent Russian troupe, the Red Star Red Army Chorus and Dance Ensemble, was recorded at the Tchaikovsky Hall in Moscow prior to a nationwide tour of the United States in the autumn of 1992. The 100-strong Ensemble was first formed within the USSR armed forces in 1997, performing concerts primarily for the army. Their repertoire ranges from popular folk tunes and songs of battle from popular folk tunes and songs of battle from all corners of the former Soviet Union to spectacular Cossack dancing and includes Glinka's Patriotic Song and Kamarinskaya, Rimsky-Korsakov's "Flight of The Bumblebee", and folk songs "Kalinka", "Dark Eyes", "A Birch Tree Stood in the Meadow", "Happy Girl" and "Seven Sons-in-Law". All are performed with energy, enthusiasm and patriotic fervour. [Cover]